Ustawowe uregulowanie statusu prawnego ochotniczych straży pożarnych - Ura, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The aim of the study is to present the legal regulations that have so far defined the legal status of an association which can be called special due to the role it plays, that is, Volunteer Fire Brigades. These are regulations contained in several acts, including the Act on Fire Protection and the Law on Associations, but the detailed scope of their tasks is specified in statutes. It has been postulated that due to the role of the Volunteer Fire Brigades, especially in the system of entities undertaking activities for fire safety, civil protection and rescue, the legal status of this organization should be regulated in a legal act. These demands were met because on 17 December 2021 the Parliament passed the Act on Volunteer Fire Brigades. The new regulations not only define the legal status of this association, but also regulate the status of volunteer firefighters, granting them certain rights in the social sphere.
Keywords: association; Volunteer Fire Brigades; legal regulations; legal status; volunteer firefighter